Oral Communication Strategies Employed by Students of International Classes at State Polytechnic of Malang among Different Personality Types - Azkia Nury Farizah (Graduate Program, University of Islam Malang, 2021)
Oral communication strategies are essential for a successful communication process. The purposes of this research are (1) to analyze the difference of oral communication strategies employed by Indonesian international class students across different personality types; (2) to investigate the types of oral communication strategies that Indonesian international class students mostly use; and (3) to explore the reasons why they employ such strategies. The subject of this study was 115 participants (69 introverts and 46 extroverts). The independent samples t-test result showed no significant difference between strategies employed by students of different personality types. Regarding speaking strategies, the students mostly employ (1) Message Alteration and Reduction strategies; (2) Non-verbal strategies; and (3) Negotiation for Meaning While Speaking strategies. Meanwhile, in listening, the students mostly employ (1) Word-Oriented strategies; (2) Scanning strategies; and (3) Non-verbal Strategies While Listening. Based on the interview results, learning environment factors, such as non-English major and international class, seem to contribute immensely to the use of oral communication strategies. The results indicated that students from both groups are determined to have a successful communication process by employing certain strategies to overcome problems that they encounter when communicating in English.